Post-harvest N2O and CO2 emissions related to plant residue incorporation of oilseed rape and barley straw depend on soil NO3- content - Köbke, Sarah; Senbayram, Mehmet; Pfeiffer, Birgit; Nacke, Heiko; Dittert, Klaus (Soil & tillage research, 2018)
•Straw is quickly decomposed and increases CO2 emissions and only to a lesser N2O emissions.•Straw-N is released only in marginal amounts as N2O from soil.•Straw amendment and N addition to wet soil (80% WHC) triggers extensive release of N2O. The sustainable production of bioenergy from crops like oilseed rape, barley, and maize presents a significant option to mitigate climate change by reducing fossil CO2 emissions. Greenhouse gas emissions (specifically N2O) during the energy crop production need to be quantified precisely for reliable life cycle analysis of bioenergy cropping systems. Energy crops (specifically oilseed rape) have a very high N demand, which results in a higher N-fertilizer application and thus higher risk of N2O emissions not only during the vegetation period but also after crop harvest due to i) incorporation of N rich plant residue to soil and/or ii) residual N. An incubation experiment was conducted under conditions favoring denitrification (80% water-holding capacity), to study the drivers of N2O emissions specifically during the post-harvest period. Here we compared two different plant residues varying in C/N ratio (oilseed rape (RST) and barley straw (BST)) with or without N supply and measured CO2, and N2O emissions. Stable isotope labeling (15N) was used to quantify soil- and residue-born N2O. Incorporation of both plant residues alone induced significant increases in CO2 emissions compared to control soil without straw addition (p < .05). However, the increase in CO2 emissions was less pronounced when straw was incorporated in conjunction with mineral N. There was a clear increase in cumulative N2O emissions (p < .05) when soil amended with BST or RST (6- and 9-fold) was compared to control, however, the increase of cumulative N2O emissions was drastic when mineral N was added (15- and 23-fold). No significant differences in N2O emission were observed when comparing residue types (p > .05). Stable isotope labeling of barley straw clearly showed that the share of residue-born N2O was very low (1.35 or 0.4%) in the overall N2O fluxes in BST and BST + N. The present study suggests that N fertilization in autumn should be avoided to minimize N2O fluxes regardless of type of straw.